Effect of Stocking Density and Marketing Age on Broiler Performance - Mohammed, Ahmed Ismael; Rashid, Saman Abdulmajid; Kirkuki, Shahla Muhammad Saeed (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was conducted at the poultry farm of faculty of Agricultural Sciences, University of Sulaimani, in Bakrajo from 5/ 12/ 2015 to 16/ 1/ 2016. The aim of this study was to determine stocking densities and marketing age on production performance, meat quantity and quality of Ross-308 broilers. Three levels of stocking density (SD) (9, 13 and17 birds/ m2) and three marketing age (28, 35 and 42 days) were used with four replication. The nine combinations were treatments as following: t1: stocking density (9 birds/ m2) + marketing age (28 days), t2: stocking density (13 birds/ m2) + marketing age (28 days), t3: stocking density (17 birds/ m2) + marketing age (28 days), t4: stocking density (9 birds/ m2) + marketing age (35 days), t5: stocking density (13 birds/ m2) + marketing age (35 days), t6: stocking density (17 birds/ m2) + marketing age (35 days), t7: stocking density (9 birds/ m2) + marketing age (42 days), t8: stocking density (13 birds/ m2) + marketing age (42 days) and t9: stocking density (17 birds/ m2) + marketing age (42 days). Stocking density and marketing age level (P≤0.05) affected on the feed intake, body weight, feed conversion ratio and body weight gain significantly at periods 28, 35 and 42 days. Effect of stocking density and marketing age on body weight, body weight gain, feed intake, feed conversion ratio and mortality were significant through all reared periods. Live body weight was significantly (P≤0.05) effected by stocking density, marketing age, sex and their interaction.
Keywords: Broiler; stocking density; marketing age; performance